Studi Literatur Berbagai Zat Warna Alam dan Ketahanannya pada Kain Batik - Christian, Jane Eunike; Susanti, Elizabeth (Telkom University, 2024)
Indonesia has a cultural heritage in the form of batik cloth that is specially made by human hands to produce a beautiful work or motif. Batik cloth coloring uses 2 types, namely natural dyes and synthetic dyes. Natural dyes do not have as good resistance as synthetic dyes, but synthetic dyes produce waste that damages nature. The use of natural dyes is in line with current movements such as Go Green, Sustainable Development Goals (SDGs), and Back to Nature. With more than 150 types of natural dyes in Indonesia, it will certainly be difficult for beginners to choose the natural dyes to use. The purpose of the study was to determine several natural dyes for batik cloth that have good resistance and how to apply them. This research is important to do because it is hoped that natural dyes will be an alternative chosen to replace synthetic substances in producing traditional Indonesian cloth while protecting the environment from waste. This research method was carried out in a descriptive-qualitative manner, namely with a literature review approach methodology for experimental journal data about dyeing batik fabric. The results of the study showed several comparisons of coloring materials in batik using natural substances that have good colorfastness; in addition, the use of natural dyes has the advantage that the longer the color, the older/more mature and beautiful it will be.